Creative Audiovisual Translation Applied to Foreign Language Education: A Preliminary Approach - Talaván, Noa (Journal of Audiovisual Translation, 2019)
Creative dubbing and subtitling are presented in this article as didactic resources to improve integrated foreign language (FL) skills (specifically oral and written production). The increasing attention that the application of audiovisual translation (AVT) to FL learning has been receiving in the last two decades calls for further exploration into the potential benefits of modern AVT modes, such as funsubbing and fundubbing, understood as the creative translation of an audiovisual text, be it into subtitles or through the production of a new audio track. After considering the educational power of creative AVT and providing the corresponding theoretical justification, the article will present a methodological proposal on how to use these AVT modes in online environments. Finally, preliminary data derived from a short-term trial will be analysed and discussed.